Prevalence of Ear and Eye Disorders in Kintamani Dog - Perayadhista, Ni Made Devityasih; Suatha, I Ketut; Puja, I Ketut (Veterinary Science and Medicine Journal, 2015)
This observational study was undertaken to evaluate the prevalence of ear and eye disorders in Kintamanidog. All data were gathered from registers of veterinary clinic located at Denpasar, Badung, and Gianyar.Various aspects concerning ear and eye disorders were collected by questionnaires. The total of Kintamanidog recorded from 2009 until 2013was 477 dogs. The result of this study showed that the prevalence ofexophthalmos (protrusion of the eye ball) and glaucoma were rare (0%), the cataract was occurred in onedog (0.2%), otitis was occurred in two dogs (0.4%), and conjunctivitis was occurred in three dogs (0.6%).All Kintamani dogs with ear and eye disorders were the male and thier ages were more than 12 months. Inconclusion, this study indicates  that the Kintamani dog has a lower problem of ear and eye disorders. In thefuture, this low prevalence of the problem hopefully can be maintained or even decreased by giving goodbreeding management.
Keywords: ear and eye disorders; Kintamani dog; prevalence